2008
DOI: 10.1038/hdy.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Array-based high-throughput DNA markers for crop improvement

Abstract: The last two decades have witnessed a remarkable activity in the development and use of molecular markers both in animal and plant systems. This activity started with lowthroughput restriction fragment length polymorphisms and culminated in recent years with single nucleotide polymorphisms (SNPs), which are abundant and uniformly distributed. Although the latter became the markers of choice for many, their discovery needed previous sequence information. However, with the availability of microarrays, SNP platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
190
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(197 citation statements)
references
References 73 publications
1
190
0
3
Order By: Relevance
“…it was found that ISSR-based cluster is more similar to the combined cluster than RAPD-based cluster [39]. Jatropha curcas also showed similar result when RAPD and ISSR dendrogram patterns were combined [40]. The result of this study showed Some private bands were detected within genotypes (Table 4).…”
Section: Principal Coordinate Analysis Of the 144mentioning
confidence: 51%
“…it was found that ISSR-based cluster is more similar to the combined cluster than RAPD-based cluster [39]. Jatropha curcas also showed similar result when RAPD and ISSR dendrogram patterns were combined [40]. The result of this study showed Some private bands were detected within genotypes (Table 4).…”
Section: Principal Coordinate Analysis Of the 144mentioning
confidence: 51%
“…The association of a particular trait of interest with a DNA polymorphism is essential for breeding purposes. Microarrays have been used to identify abundant DNA polymorphisms throughout the genome (Gupta et al 2008;Hazen and Kay 2003). In particular, ELPs and SFPs can be identified from RNA hybridization studies.…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) have become the marker of choice because of their abundance and uniform distribution throughout the genome (Gupta et al 2008;Varshney et al 2005;Zhu and Salmeron 2007). Around 90% of the genetic variation in any organism is attributed to SNPs (Varshney et al 2005;Zhu and Salmeron 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently from the previous cited markers, the definition of single nucleotide polymorphism is not dependent on the methodology used for their detection, which can be various. The most efficient are oligonucleotide arrays (Gupta et al, 2008). Similarly, small insertion or deletion (INDEL) have been localized and their frequencies measured (Zhidkov et al, 2011).…”
Section: Sequencing and Single Nucleotide Polymorphismmentioning
confidence: 99%